SME mining reference handbook - Lowrie, Raymond L. (Society for Mining, Metallurgy, and Exploration, 2002)
Engineers are often called on to answer technical questions and solve problems while in the field. It's not always feasible to bring along the bulky reference materials needed to research engineering-related topics. Now there's a simple solution. The SME Mining Reference Handbook is a practical field reference for mining and minerals engineers who spend time away from the office. With its comprehensive store of charts, graphs, tables, equations, and rules of thumb, the handbook is the essential technical reference for mobile mining professionals. It's also a convenient desk reference for in-of.